Readiness of UV Express Operators for the Public Utility Vehicle Modernization Program (PUVMP) in the Province of Albay - Lantican, Cherry (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the readiness of UV Express operators in the First District of Albay to comply with the Public Utility Vehicle Modernization Program (PUVMP). Anchored on the Innovation Diffusion Theory, Socio-Technical Systems Theory, Organizational Change Management Theory, and the Resource-Based View, the study examined operators' level of awareness, operational practices, readiness of consolidated public transportation entities, anticipated implementation challenges, and support mechanisms for successful modernization. A descriptive quantitative research design using a prospective approach was employed. Data were collected through two self-made, non-standardized survey questionnaires administered to 61 UV Express operators and 25 key informants from five consolidated transportation entities. Descriptive statistics, weighted mean, and a five-point Likert scale were used to analyze the data. The findings revealed that operators generally demonstrated high awareness of the PUVMP, positive operational practices, and willingness to comply with modernization requirements. Consolidated entities were found to be generally well prepared in terms of technical proficiency and operational management but only moderately ready in financial capacity. Financial, operational, and regulatory concerns, particularly the high cost of modernization, limited financial resources, and compliance requirements, remained the major challenges affecting implementation. The study further identified government financial assistance, technical support, institutional guidance, and private sector participation as essential mechanisms for facilitating a smooth transition. Overall, the study concluded that successful implementation of the PUVMP requires strengthened financial, technical, organizational, and institutional support to enhance operators' readiness and promote sustainable public transportation. Future studies are encouraged to examine implementation across different regions and operator types, investigate specific implementation challenges qualitatively, and assess the long-term economic impacts of the modernization program. This study supports Sustainable Development Goal (SDG) 9: Industry, Innovation and Infrastructure, SDG 11: Sustainable Cities and Communities, and SDG 13: Climate Action by examining transport modernization, sustainable mobility, and cleaner public transportation. Its findings contribute to transportation policy, institutional planning, and sustainable mobility by providing evidence that may guide government agencies, transport cooperatives, and other stakeholders in strengthening modernization strategies while improving transport services and supporting operators' transition.
Keywords: Awareness; Operational Practices; Public Utility Vehicle Modernization Program; Readiness; Sustainable Transportation; UV Express Operators